Water Quality Factors and Impacts - Dunea, Daniel (IntechOpen, 2022)
This book provides a comprehensive overview of the factors and impacts influencing water quality in various locations worldwide. It discusses the use of new analytical and monitoring methods and novel technologies for decontamination and protection of polluted waters. It includes three sections that discuss monitoring and assessment of water quality, factors of water quality degradation, and methods for water quality improvement. Water quality is a global environmental concern affecting the socioeconomic development and functionality of various ecosystems. The protection of water quality requires adequate monitoring and assessment methods included in reliable watershed management plans.